Seismic Vibration Mitigation of Wind Turbine Tower Using Bi-Directional Tuned Mass Dampers. (2nd December 2020) - Li, Wanrun; Zhang, Qing; Yang, Zhou; Zhu, Qingxin; Du, Yongfeng
Abstract : Wind turbines have been increasingly erected in earthquake regions to harvest abundant wind energy. However, the wind turbine tower is slender and lightly damping, which exhibits high susceptibility to earthquake-induced vibration. It is challenging to mitigate the seismic vibration of the tower. In this study, a bi-directional tuned mass damper (BTMD) is proposed to mitigate the seismic vibration of the wind turbine tower. Meanwhile, a lumped-mass finite element model (LFEM) and a coupled blade tower finite element model (CBFEM) are used to investigate the vibration mitigation performance of the BTMD. First, the BTMD and corresponding dynamic equilibrium equations are systemically introduced. Accordingly, the optimum stiffness and damping of the BTMD at different mass ratios are investigated. Then, the dynamic prosperities of the LFEM and CBFEM are compared. Subsequently, the seismic responses of the wind turbine with the BTMD are conducted using the LFEM and CBFEM. Meanwhile, the mitigation performances of the BTMD under uni- and bi-directional earthquakes are investigated. The displacement, acceleration, and bending moment of the wind turbine tower are analyzed in time domain and frequency domain. Note that the influential factors, including mass ratio and structural frequency, on the vibration mitigation performance of the BTMD are investigated. Results show that the proposed BTMD can significantly mitigate the peak values of the top displacement and bottom bending moment. However, the blade tower coupling effect and frequency variation of the tower would have influences on the mitigation efficiency of the BTMD. The results enable a better understanding of the seismic vibration mitigation of the wind turbine tower using tuned mass dampers.